Resistin gene expression in visceral adipose tissue of postmenopausal women and its association with insulin resistance. (September 2012) - Sadashiv,; Tiwari, Sunita; Paul, Bhola Nath; Kumar, Sandeep; Chandra, Abhijit; Dhananjai, S; Negi, Mahendra Pal Singh
Aim: The present study evaluates resistin mRNA expression in visceral adipose tissue (VAT) and its correlation with insulin resistance (homeostatic model assessment) in postmenopausal obese women.Materials & methods: A total of 68 (nonobese = 34 and obese = 34) age-matched (49–70 years) postmenopausal women were recruited for the study. Fasting blood samples were collected at admission and abdominal VAT were obtained during surgery for gall bladder stones or hysterectomy. Physical parameters (age, height, weight and BMI) were measured. Biochemical parameters (plasma insulin, plasma glucose and serum resistin) were estimated by enzymatic methods. The VAT resistin mRNA expression was evaluated by real-time PCR.Results: The relative mean (± standard deviation) VAT resistin mRNA expression in postmenopausal obese women lowered significantly by 20.4% compared with postmenopausal nonobese women (0.029 ± 0.011 vs 0.023 ± 0.013; p = 0.047). Furthermore, VAT resistin mRNA expression in postmenopausal obese women was downregulated by 0.69-fold when compared with age-matched postmenopausal nonobese women. Furthermore, the relative VAT resistin mRNA expression in postmenopausal obese women showed significant inverse association with insulin resistance (r = -0.48; p < 0.01) and serum resistin (r = -0.84; p < 0.001), while in postmenopausal nonobese women it did not show any association with both insulin resistance (r = 0.03; p > 0.05) and serum resistin (r = -0.03; p > 0.05).Conclusion: The VAT resistin mRNA expression in postmenopausal obese women is associated to insulin resistance.